Development of the integrated fish endocrine disruptor test: part B: dimplementation of thyroid-related endpoints - Gölz, Lisa; Pannetier, Pauline; Fagundes, Teresa; Knörr, Susanne; Behnstedt, Laura; Coordes, Sara; Matthiessen, Peter; Morthorst, Jane; Vergauwen, Lucia; Knapen, Dries; Holbech, Henrik; Braunbeck, Thomas; et al. (Integrated environmental assessment and management, 2023)
Given the vital role of thyroid hormones (THs) in vertebrate development, it is essential to identify chemicals that interfere with the TH system. Whereas, among nonmammalian laboratory animals, fish are the most frequently utilized test species in endocrine disruptor research, for example, in guidelines for the detection of effects on the sex hormone system, there is no test guideline (TG) using fish as models for thyroid-related effects; rather, amphibians are used. Therefore, the objective of the present project was to integrate thyroid-related endpoints for fish into a test protocol combining OECD TGs 229 (Fish Short-Term Reproduction Assay) and 234 (Fish Sexual Development Test). The resulting integrated Fish Endocrine Disruption Test (iFEDT) was designed as a comprehensive approach to covering sexual differentiation, early development, and reproduction and to identifying disruption not only of the sexual and/or reproductive system but also the TH system. Two 85-day exposure tests were performed using different well-studied endocrine disruptors: 6-propyl-2-thiouracil (PTU) and 17α-ethinylestradiol (EE2). Whereas the companion Part A of this study presents the findings on effects by PTU and EE2 on endpoints established in existing TGs, the present Part B discusses effects on novel thyroid-related endpoints such as TH levels, thyroid follicle histopathology, and eye development. 6-Propyl-2-thiouracil induced a massive proliferation of thyroid follicles in any life stage, and histopathological changes in the eyes proved to be highly sensitive for TH system disruption especially in younger life stages. For measurement of THs, further methodological development is required. 17-α-Ethinylestradiol demonstrated not only the well-known disruption of the hypothalamic-pituitary-gonadal axis, but also induced effects on thyroid follicles in adult zebrafish (Danio rerio) exposed to higher EE2 concentrations, suggesting crosstalk between endocrine axes. The novel iFEDT has thus proven capable of simultaneously capturing endocrine disruption of both the steroid and thyroid endocrine systems. Integr Environ Assess Manag 2023;00:1-16. © 2023 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC).
Gesehen am 29.11.2023